Dynamics of deforestation in the northwest of the Chaco between 1995 and 2018 - Fernando Bonfanti; Matías Sánchez (Boletín Geográfico)
This paper has been prepared within the framework of the project: “Territorial transformations in the province of Chaco: forestry and agricultural dynamics in the transition of the twentieth and twenty-first centuries and their geographical implications”, developed at the Geography Institute of the Faculty of Humanities of Universidad Nacional del Nordeste. The project objective, it’s to analyze the forest dynamics of the two northwestern departments of Chaco province taking into account the occurrence of deforestation. The present paper presents the analysis of deforested areas in the northwestern Chaco, considering the current National and provincial legislation on the subject, and the state of art literature as a basis. The paper presents basic cartography that was obtained employing an analytical and descriptive methodology using a Geographic Information System. Broadly speaking, the changes observed in forested areas were the result of the pressure that man makes over the productive space. The actual concern is that the state of deforestation in the Chaco province is influenced by the deficiencies and irregularities in the implementation of the Law of minimum budgets of territorial planning of native forests (ley 26331). For this reason, this work could be a valuable contribution for those organisms that are dedicated to the management of our forests and contribute to stop the advance of deforestation, leaving aside the economic interests and admitting the serious consequences that this entails in environmental material.